THE IMPLICATIONS OF VIRTUAL COMMUNICATION IN MANAGING THE COVID-19 PANDEMIC NEW CULTURAL NORMS: A CASE STUDY IN THE NORTHWEST COAST OF SABAH - Halina Sendera Mohd Yakin,; Kwan Yien Yee,; Odetta Yahcob,; Andreas Totu,; Suraya Sintang,; Siti Hasnah Tanalol, (Journal of Islamic, Social, Economics and Development, 2021)
The Covid-19 pandemic that swept people across the world brings an inevitableimpact on various aspects of life. This has sparked a new norm that promotes the importanceas well as the need and dependence on virtual communication for the social life that is no longercompatible with the old norms that are conventional in nature. The main objective of this paperis to examine the implications of virtual communication on rural communities in Sabah duringthe Covid-19 pandemic by identifying the forms of challenges, contributing factors andadaptation mechanisms that are being practiced. Field studies were conducted at Kudat, KotaMarudu and Pitas districts in North West Coast of Sabah, Malaysia using the combination ofboth qualitative and quantitative methods, namely participant observation, interviews andquestionnaire. The findings found that the challenges or problems faced by the community thatare related to the implications of virtual communication involve aspects of teaching andlearning, online transactions, career-related matters, daily routines and social relationships.Apart from physical factors such as hill landforms and forest-covered terrain, other factorssuch as economic status, social relationships, administrative enforcement as well as personal aspects such as perceptions, motivation and individual skills also have a significant impact onthe challenges and problems of virtual communication among the rural communities.Individuals and organization involved have taken initiatives and implemented several strategiesto address these issues. It is hoped that the findings of this paper can contribute usefulrecommendations with regard to the implications of virtual communication to all partiesconcerned in dealing with any related issues in the future.